OPEN BANKING FOREIGN EXPERIENCE, ITS ESSENCE AND ADVANTAGES - Yuryevna, Arzumanyan Stella; Samukdjanovna, Azimova Shakhnoza (International Journal of Psychosocial Rehabilitation, 2020)
This article is devoted to questions of the essence of open-banking, its advantages, foreign experience in its application, prospects for its implementation in the practice of domestic banks.